CÖNK” TERİMİ VE CÖNKLER ÜZERİNE BİR BİBLİYOGRAFYA DENEMESİ - (:unkn) unknown (My University, 2015)
Cönkler, genellikle şairi bilinen şiirlerle birlikte türkü, mani, destan, fıkra, hikâye, duâ, hutbe gibi yazanı belli olmayan manzûm ve mensûr metinlerin, hastalıkların tedavisinde kullanılan ilaç tariflerinin, sosyal hayatta iz bırakan ve ya cönkün derleyicisi tarafından önemli görülen olay ve olguların kayıtlarının, günlük hayatı kolaylaştıracak faydalı bilgilerin, dinî kaide ve öğütlerin yer aldığı not defterleridir. Her çeşit edebî, tarihî, kültürel ve folklorik ürünleri içeren cönkler, muhtevalarında barındırdıkları zenginlik sebebiyle edebiyat tarihinde büyük bir boşluğu doldurmaktadır. Çeşitli bilgi ve metinleri edebiyatımıza kazandıran en önemli kaynaklardan biri olan cönkler, manzûm ve mensûr metinlerin mukayeseli şekilde oluşturulmasında bir nüsha olarak edebiyat tarihinin asıl kaynaklarına yardımcı olduğu gibi, manzûm ve mensûr metinlerin tek nüshası, tarihi olay ve olguların tek tanığı, folklorik ürünlerin geleceğe taşınmasında kültür taşıyıcısı olarak asıl kaynak görevi de üstlenmektedirler. Bu çalışmada, "cönk" kelimesinin kökeni hakkında ileri sürülen görüşler doğrultusunda kelimenin kökeninin ne olduğunu belirlemeye çalıştık. Sözlüklerden, ansiklopedilerden ve akademik çalışmalardan hareketle "cönk" kelimesinin anlam çerçevesini belirlemeye çalıştık. Bu sebeple, ulaşabildiğimiz her türlü ilmî kaynakta yer alan cönk tanımlarını, anlam ilişkisi bakımından birbirleriyle karşılaştırarak anlamsal bir bütünlük kurmaya çalıştık. Daha sonra, "cönk" kelimesinin tarihî süreç içerisinde, hangi uluslarda hangi anlamlara geldiğini, hangi kavramlar ve nesneler için kullanıldığını, kullanılmaya başlanıldığı tarihten günümüze kadar hangi kelimelerle târif edildiğini karşılaştırma ve tartışmalar halinde sunmaya gayret gösterdik. Cönkler üzerine yaptığımız araştırmalarda şimdiye kadar kapsamlı bir bibliyografya çalışmasına rastlamadığımız için yazıya bir bibliyografya ekleyerek elde ettiğimiz verileri, bizden sonra cönkler üzerine bilimsel faaliyette bulunacak araştırmacıların istifadesine sunmayı hedefledik. Bibliyografyada verilen çalışmaları, doğrudan cönkler hakkında yapılmış çalışmalar (transkripsiyonlu metin-tanıtıminceleme), cönklerin önemi/işlevi üzerine yapılmış çalışmalar ve cönklerin katkısıyla şair ve şiirleri hakkında yapılmış yayınlar oluşturmaktadır. Elde ettiğimiz veriler ışığında birer "kırk ambar" ve "kültür hazinesi" olarak görülen cönklerin Türk Edebiyatında ve Türk kültüründeki yerini belirlemeye çalıştık

Junks are notebooks which include poems by known poets and ballads, folk songs, legends, jokes, stories, prayers and sermons. Beside, prose and poetry texts whose poets are unknown, medicine recipes, beneficial knowledge about daily life, religious pedestals and advices, important events of daily life which are chosen by the author of the junk also take place in these notebooks. Since junks contain all sorts of literary, historical, cultural, folkloric products, they have remarkable place in literature history. Being an important source that brings all sorts of knowledge and texts together it helps main sources of literature about classification of prose and poetry texts. In addition to these, junks are the only copy and witness of these historical, cultural and folkloric products and carry them into the future. In that sense junks can be regarded as main source, too. In this paper, origin of the term “junk” is tried to be determined in the light of the arguments stated earlier. Considering the dictionaries, encyclopaedias and academic works the meaning of the word “junk” is tried to be adjusted. For this reason each definition of the term that is found in available scientific sources are examined in detail in terms of their meanings. Then, it is searched that the word junk is used by which nations and means what along history. According to our research on junks, there is no comprehensive bibliography study on it so far. Therefore a bibliography is added to paper in order to later researchers can be benefited from our data while having their scientific study on this subject. In the light of the data we get, the significance of junk which is regarded as “stores” and “cultural treasure” in Turkish literature is tried to be determined Junks are notebooks which include poems by known poets and ballads, folk songs, legends, jokes, stories, prayers and sermons. Beside, prose and poetry texts whose poets are unknown, medicine recipes, beneficial knowledge about daily life, religious pedestals and advices, important events of daily life which are chosen by the author of the junk also take place in these notebooks.Since junks contain all sorts of literary, historical, cultural, folkloric products, they have remarkable place in literature history. Being an important source that brings all sorts of knowledge and texts together it helps main sources of literature about classification of prose and poetry texts. In addition to these, junks are the only copy and witness of these historical, cultural and folkloric products and carry them into the future. In that sense junks can be regarded as main source, too. In this paper, origin of the term “junk” is tried to be determined in the light of the arguments stated earlier. There are three different views. According to one of these views, the term junk comes from “Cava” and “Malaya” languages while the other argues that it comes from Hindi and third one says it comes from Turkish. Considering the dictionaries, encyclopaedias and academic works the meaning of the word “junk” is tried to be adjusted. For this reason each definition of the term that is found in available scientific sources are examined in detail in terms of their meanings. Then, it is searched that the word junk is used by which nations and means what along history. Following the searches about the term “junk”, there are names such as “big sealing vessel”, “leather notebook”, “poetry journal”, “notebook”, “manuscript notebook”, “manuscript journal”, “journal”, “poetry notebook”, “huge boat”, “folk poetry journal”, “cow language”, “calf language”, “a kind of Chinese boat”, “great galley”, “book”, “joker”, “smiling face”, “corner”, “bliss”, “cheerful”, “richness”, “huge object”, “fortune”, “wealth”, “white notebook”, “long notebook”, “song journal” for the term “junk”. According to our research on junks, there is no comprehensive bibliography study on it so far. Therefore a bibliography is added to paper in order to later researchers can be benefited from our data while having their scientific study on this subject. Studies in bibliography are divided into titles as followings; Studies on junks, studies on importance of junks and Studies about poets and poetry that is prepared with the contributions of junks. Tags, books, thesis, articles and assertions are given with their titles in our bibliography. There are master and doctorate’s thesis. Both in thesis and others’ names no grammatical redaction is made. According to bibliography study we made, there are 12 books, 19 thesis and 131 articles about “junks”. In the light of the data we get, the significance of junk which is regarded as “stores” and “cultural treasure” in Turkish literature is tried to be determined
THE TERM “JUNK” AND A BIBLIOGRAPHY STUDY ON JUNKS